Perbandingan Kecepatan Pencarian Data SQL dan NOSQL - Muhammad Firdaus Abdi; Agung Susanto; Kusnawi Kusnawi (Universitas Asahan, 2021)
Abstract - The development of database technology requires a quality of data, where a database is needed in various applications that support the performance of a company or office, so that the database is said to be good, it must be managed appropriately, efficiently in terms of speed or time. For this reason, the use of this database is still the prima donna used in running a system. In this study, testing a database to determine the query response time from a Structured Query Language (SQL) and NoSQL (Non-SQL) system which was tested with a sales or sales database where the data records were (100,500,1000,100000, 2279879). Testing focused on data search includes queries displaying all data, one of the data, AND, OR, AND and OR, Order By (asc), and Order By (desc). The purpose of this research is to produce a comparative analysis of the query response time between SQL and NoSQL so that it is known which database is superior in a data search for use. The results of this study indicate that NoSQL is superior in searching for a database, but there are certain NoSQL searches that are slower than the SQL search process. Keywords - NoSQL, SQL, Response Time, Search Data, Comparison Base Data. Abstrak – Perkembangan teknologi basis data dituntut sebuah kualitas sebuah data, yang dimana sebuah basis data sangat diperlukan di berbagai aplikasi penunjang kinerja sebuah perusahaan atau kantor, untuk itu agar basis data dikatakan baik harus dikelola dengan tepat, efesien dari segi kecepatan atau waktu. Untuk itu penggunaan basis data ini masih menjadi primadona digunakan dalam menjalankan sebuah sistem. Pada penelitian ini melakukan pengujian sebuah database untuk menentukan waktu query response dari sebuah sistem Structured Query Language (SQL) dan NoSQL(Non SQL) yang diujikan dengan database sales atau penjualan yang dimana record data (100,500,1000,100000, 2279879). Pengujian terfokus pada pencarian data meliputi query tampil seluruh data, salah satu data, AND, OR, AND dan OR, Order By (asc), dan Order By (desc). Tujuan penelitian ini menghasilkan analisis perbandingan waktu query response antara SQL dan NoSQL agar diketahui basis data yang lebih unggul dalam sebuah pencarian data untuk digunakan. Hasil penelitian ini didapat bahwa NoSQL lebih unggul dalam pencarian sebuah datam namun ada pencarian tertentu NoSQL lebih lambat dari proses pencarian SQL. Kata Kunci - NoSQL,SQL, Response Time,Pecarian Data,Perbandingan Basis Data.